Evaluation of the increase in orthodontic treatment demand in adults - Eduardo César Werneck; Fernanda Silva Mattos; Márcio Garcia da Silva; Renata Falchete do Prado; Adriano Marotta Araújo (Brazilian Dental Science)
Preventive measures in Dentistry and the modernization of the orthodontics appliances led adult patients to seek orthodontic treatment to improve their appearance and social acceptance, as well as function and oral health. Adult patients present some peculiarities such as periodontal disease and tooth loss which complicates the mechanotherapy, requiring a multidisciplinary team and a more complex mechanics. Thus, the aim of this study was to verify the proportion of young and adult patients who started orthodontic treatment in the period from 2000 to 2010, as well as the total percentage, and to correlate male and female values. The sample of 3,272 patients was divided into three groups according to the age: up to 20 (group 1), from 20 to 40 (group 2) and above 40 years-old (group 3), according to gender. It was found that most patients were young (group 1: 71.85%). However, the number of adults from 20 to 40 years-old represents a considerable share of 26.52%. Above 40 years-old, 1.61% patients sought for orthodontic treatment. If we consider the patient in the age-range above 20 years-old as adult, there was a considerable increasing in the values from 12.14%, in 2000 to 27.81% in 2010, especially in females (31.26%), mainly in groups 2 and 3, showing that dental aesthetics is an important factor for the individual social insertion.